Speed estimation of rotating machinery using generated harmonics. (November 2018) - Singh, Gurmeet; Kumar, T. Ch. Anil; Naikan, V. N. A
Highlights: Vibration monitoring is applied for speed estimation of rotating machinery. Vibration spectrum with sample of short duration produces large error in speed estimation. Speed estimation using harmonic component improve its accuracy. However, higher harmonics component are found to be absent in many cases. An algorithm is proposed to generate artificially higher order harmonic components of the fundamental rotational frequency, for speed estimation. Accurate speed estimation using the proposed algorithm reduces error in estimating speed by 16 times. Abstract: The use of vibration sensors for rotational speed estimation has been found to be an effective and reliable technique. In general, the fundamental rotational frequency ( f ) component observed in the vibration spectrum represents the rotational speed. However, for a better accuracy of estimation, large sample duration is required which results in a higher data acquisition time, computational time and data storage. Hence, the estimation of speed accuracy with the vibration signal of a short duration is a challenging task. This paper proposes an algorithm, which requires extraction of the fundamental rotational frequency component and later, the artificial generation of its corresponding harmonic components, for the accurate estimation of speed. The proposed algorithm can be used to estimate the speed of any rotating machinery.